Back Cover: Advanced Engineering Materials 4∕2018. Issue 4 (18th April 2018) - Unknown
Abstract : The new method of the quantitative analysis for retained austenite in steels by neutron diffraction is proposed. This approach is based on the calibration with reference samples in order to reliably evaluate low fractions of retained austenite in textured steels. Experiments were fulfilled at pulsed nuclear reactor IBR–2 (Dubna, Russia) in the Laboratory founded by the Nobel prize winner Ilya Frank. Further details can be found in the article1700559 by Dmitry Nikolayev and co‐workers.